A Rosato & Associates Novel - Scottoline, Lisa (New York, 2013)
"New York Times bestselling and Edgar Award-winning author Lisa Scottoline revolutionized crime fiction when she introduced her all-female law firm of Rosato & Associates, thrilling readers with her twisty, fast-paced plots and capturing their hearts with her cast of strong yet totally relatable female characters. Fans have been clamoring for more stories with the characters they've come to know and love, so Bennie Rosato, Mary DiNunzio, Judy Carrier, and Anne Murphy are back with all cylinders firing in Accused. They'll face their most challenging and dangerous case ever. It begins with an astonishing request from a thirteen-year-old prospective client. Allegra Gardner's sister Fiona was murdered six years ago. It seemed like an open-and-shut case: the accused, Lonnie Stall, was seen fleeing the scene; his blood was on Fiona and her blood was on him; most damningly, Lonnie Stall pleaded guilty. But Allegra believes Lonnie is innocent and has been wrongly imprisoned. Taking on the case seems foolhardy to Mary DiNunzio, because the Gardner family is one of the richest and most powerful in the country and Allegra's parents do not believe in reopening this case. But the Rosato & Associates firm can never resist an underdog. Was justice really served all those years ago? It will take a team of unstoppable female lawyers, plus one thirteen-year-old genius, to find out. Accused kicks off an annual fall series featuring the new adventures of Rosato & Associates, delivering all the emotion, action, and humor we've come to expect from one of the best writers in the business.From The New York Times bestselling author comes a much-anticipated new thriller featuring the all-female law firm, Rosato & Associates "--
"New York Times bestselling and Edgar Award-winning author Lisa Scottoline revolutionized crime fiction when she introduced her all-female law firm of Rosato & Associates, thrilling readers with her twisty, fast-paced plots and capturing their hearts with her cast of strong yet totally relatable female characters. Fans have been clamoring for more stories with the characters they've come to know and love, so Bennie Rosato, Mary DiNunzio, Judy Carrier, and Anne Murphy are back with all cylinders firing in Accused. Their most challenging and dangerous case ever begins with an astonishing request from a thirteen-year-old prospective client. Allegra Gardner's sister Fiona was murdered six years ago. It seemed like an open-and-shut case: the accused, Lonnie Stall, was seen fleeing the scene; his blood was on Fiona and her blood was on him; most damningly, Lonnie Stall pleaded guilty. But Allegra believes Lonnie is innocent and has been wrongly imprisoned. Taking the case seems foolhardy to Mary DiNunzio, because the Gardner family is one of the most powerful in the country and Allegra's parents do not believe in reopening it. But the Rosato & Associates firm can never resist an underdog. Was justice really served all those years ago? It will take a team of unstoppable female lawyers, plus one thirteen-year-old genius, to find out. Accused kicks off an annual fall series featuring the new adventures of Rosato & Associates, delivering all the emotion, action, and humor we've come to expect from one of the best writers in the business"--
Booklist
Publishers Weekly
Library Journal
Kirkus Reviews
Adult.
Adult.
Keywords: Offenses against the person; Fiction; Legal stories; Adventure fiction; Fiction; Fiction; Fiction; Homicide; Women lawyers; Fiction; Rosato & Associates (Imaginary organization); Criminal investigation